2014
DOI: 10.1111/jgs.12979
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric Emergency Department Innovations: Preliminary Data for the Geriatric Nurse Liaison Model

Abstract: for the GEDI-WISE InvestigatorsOlder adults account for a large and growing segment of the emergency department (ED) population. They are often admitted to the hospital for nonurgent conditions such as dementia, impaired functional status, and gait instability. The aims of this geriatric ED innovations (GEDI) project were to develop GEDI nurse liaisons by training ED nurses in geriatric assessment and care coordination skills, describe characteristics of patients that these GEDI nurse liaisons see, and measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
93
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(101 citation statements)
references
References 12 publications
4
93
0
4
Order By: Relevance
“…Evidence of the efficacy of health service interventions aimed at providing appropriate care for ageing populations is present in the literature with varying levels of success reported [9][10][11][12][13][14][15][16][17][18]. Some examples of these interventions are: improving care in RACFs via change in staffing models most often to include a Nurse Practitioner [11], interventions in EDs for presentation of older people, and outreach models from health services to the community most often provided by nurses, hospital in the home (HITH) and hospital in the nursing home (HINH).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence of the efficacy of health service interventions aimed at providing appropriate care for ageing populations is present in the literature with varying levels of success reported [9][10][11][12][13][14][15][16][17][18]. Some examples of these interventions are: improving care in RACFs via change in staffing models most often to include a Nurse Practitioner [11], interventions in EDs for presentation of older people, and outreach models from health services to the community most often provided by nurses, hospital in the home (HITH) and hospital in the nursing home (HINH).…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to keep frail older persons at their place of residence during an acute illness, several MOC have been designed and tested. Broadly, the different MOC are divided into those that: i) provide in-home care or outreach of services from one service to another [12, 24, 27, 28]; ii) provide prioritisation or geriatric focused care in the ED [2932]; or iii) support or enhance primary care [28, 33]. …”
Section: Introductionmentioning
confidence: 99%
“…Although the experiences of other countries have found positive results with the implementation of practices by nurses, it should be pointed out that they are linked to a multidisciplinary approach and, for the most part, are inserted into care models and welfare programs geared toward the elderly (5,16,18) . Another question that did not reach consensus was related to the need of a specialized interdisciplinary team in gerontology/geriatrics to support cases of high-risk and fragile elderly people.…”
Section: 6mentioning
confidence: 99%
“…The experiences described by care programs have demonstrated that, through appropriate geriatric assessments, identification of risks, and support strategies in the transition of the care, it is possible to reduce the return of the elderly to the ES, avoid admissions, obtain greater satisfaction, and reduce hospital costs (5,16,(18)(19) . Therefore, these studies offer different examples that can encourage new practices in the ES together with the reality of each institution.…”
Section: 6mentioning
confidence: 99%
See 1 more Smart Citation